The Role of International Cooperation in the Enforcement of Anti-Terrorism Laws - Gracesy Prisela Christy; Wahyudi; Tomi Apra santosa; Mira Nila Kusuma Dewi (Faculty of Law, Universitas Pekalongan, 2025)
This study examines the role of international cooperation in anti-terrorism law enforcement in response to the complexity of terrorism threats that are transnational and transnationally organized. Using normative research methods that focus on the analysis of laws and regulations and international legal instruments, this study examines the effectiveness of cooperation mechanisms between countries in strengthening law enforcement and preventing acts of terrorism. The findings of the study show that international cooperation, through intelligence exchange, legal harmonization, extradition, and technical capacity building of law enforcement officials, makes a significant contribution to strengthening the effectiveness of anti-terrorism law enforcement. However, challenges in the form of differences in political interests, domestic legal constraints, and state sovereignty issues are still the main obstacles. This study recommends strengthening inclusive cooperation mechanisms based on respect for international norms as a strategic step to deal with the dynamics of terrorism threats globally. Thus, international cooperation is not only a tool of law enforcement but also a key element in terrorism prevention strategies.